Application of Hot Water Dip in Reducing Chilling Injury of Banana Cv. Berangan During Low Temperature Storage - Ratule, Muhammad Taufiq (2006)
‘Berangan’ banana (Musa sapientum cv. Berangan), being an extremely perishable commodity, requires low temperature storage before sale or consumption. However, chilling injury (CI) symptoms were exhibited when exposed to very low temperatures. Hot water dip (HWD) has been recognized able to alleviate CI symptoms. The reduction of sensitivity to CI by HWD could be due to the induction of heat shock proteins (HSP) and polyamines (PA) which protected the lipid peroxidation in membrane lipids. In the present study, the CI symptoms developed in Berangan banana were characterized. The banana was then treated with HWD in order to reduce the CI development. The HSP and PA contents were identified to determine the causal factor contributing to CI reduction in HWD-treated banana. The peroxidation of membrane lipids in relation to reduction of CI in HWD-treated banana was also assessed.